A behavioral approach to asset pricing - Shefrin, Hersh, 1948- (Academic Press advanced finance series., 2005)
A Behavioral Approach to Asset Pricing Theory examines the reigning assumptions of asset pricing theory and reconstructs them to incorporate findings from behavioral finance. It constructs a solid, intact structure that challenges classic assumptions and at the same time provides a strong theory and efficient empirical tools. Building on the models developed by both traditional asset pricing theorists and behavioral asset pricing theorists, this book takes the discussion to the next step. The author provides a general behaviorally based intertemporal treatment of asset pricing theory that extends to the discussion of derivatives, fixed income securities, mean-variance efficient portfolios, and the market portfolio. The book develops a series of examples to illustrate the theoretical results. The CD-ROM contains most of the examples, worked out as Excel spreadsheets, so that a diligent reader can follow them through. Instructors might also want to use the examples to assign class exercises, asking students to modify the numbers and see what happens.